Cesarean section history affects the outcomes of frozen embryo transfer in IVF/ICSI: a retrospective study - Wang, Xiaohui; Zhou, Yan (Frontiers in Surgery, 2025)
ObjectiveCesarean section (CS) rates have risen globally, with cesarean scar defect (CSD) being a common complication. Few studies have investigated the impact of CSD on in vitro fertilization/intracytoplasmic sperm injection frozen embryo transfer (IVF/ICSI-FET) outcomes. This study assessed how prior CS history (with or without CSD) affects IVF/ICSI-FET outcomes compared with prior vaginal delivery (VD).MethodsWe retrospectively analyzed 985 IVF/ICSI-FET patients: 597 patients with prior VD (VD group) and 388 with prior CS (CS group). The CS group was subdivided into those without CSD (NCSD, n = 283) and those with CSD (CSD, n = 105). Binary logistic regression was used to assess the associations between delivery history and pregnancy outcomes.ResultsNo significant differences in early abortion, premature birth, perinatal complications or birth weight were detected between the VD and CS groups. However, compared with the VD group, the CS group had significantly lower biochemical pregnancy, implantation, live birth, and clinical pregnancy rates. Among women with prior CS, the CSD group had significantly higher rates of premature birth and perinatal complications than the NCSD group did. The size of the CSD did not affect the live birth rate or clinical pregnancy rate.ConclusionsPrior CS negatively affects IVF/ICSI-FET pregnancy outcomes. The presence of CSD further increases premature birth and perinatal complication rates.